Development and correlations of the industrial ecology in China's Loess Plateau: A study based on the coupling coordination model and spatial network effect. (December 2021) - Sun, Yifang; Wang, Ninglian
Graphical abstract: Highlights: Define IE as an evolutionary process characterized by the dimensions of industry and ecology. Industrial efficiency and eco-efficiency were analyzed from spatial-temporal perspectives. Cities were classified as coordinated development mode and professional development mode. Social network analysis was used to examine the spatial correlations of IE. The IE interaction network was characterized by "scale-free" and "small world." Abstract: Industrial ecology (IE) was defined as a dynamic evolution process characterized by the coupling coordination relationship between ecological efficiency and industrial efficiency. This paper used data envelopment analysis and technique for order preference by similarity to ideal solution method to explore the spatiotemporal evolution of ecological efficiency and industrial efficiency in China's loess plateau region (LPR) from 2006 to 2017. Based on the definition, LPR's IE development and spatial correlations were studied separately using coupling evaluation model and social network analysis. Findings include: Although eco-efficiency and industrial efficiency were mutually promoted, and both have improved during the study period, LPR's human-earth relation was still facing uncertainties. There were significant disparities in industrial efficiency, ecological efficiency, and IE levels among cities. The evolutionary patterns of cities were classified as coordinated development mode and professional development mode. The IE interactive network was characterized by "scale-free" and "small world, " where provincial capitals and big cities functioned as growth poles and intermediaries. The correlations of IE brought challenges as well as favorable conditions for setting up a cross-regional coordination mechanism. This paper provided a new perspective to understand IE and a "quantity and structure" driven development idea for policymakers.